Effect of Addition of Probiotics with Different Doses in Commercial Feeds on Growth and Life Passage of Baung Fish (Hemibagrus nemurus) in Aquaponic Recirculation Systems - Rijen Rio; Usman M Tang; Niken Ayu Pamukas (Jurnal Akuakultur SEBATIN, 2023)
This research was carried out in April 2022 - May 2022 which took place at the Aquaculture Technology Hatchery. The purpose of the study was to determine the best probiotic bioflocculant dose in feed to increase growth and survival of baung fish. This study used a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatment in this study was the addition of probiotic bioflocculants to commercial feed, namely P0 control (without adding probiotics), P1 (5 ml/kg feed), P2 (10 ml/kg feed), P3 (15 ml/kg feed). The results showed that the addition of a probiotic bioflocculant 15 ml/kg of feed was the best result which resulted in an absolute weight growth of 4.04 g, an absolute length growth of 3.17 cm, a specific growth rate of 2.65%, and a survival rate of 97.61%. Water quality parameters during the study were temperature 26-27 0C, pH 6-7 ppm, DO 4.12-5.57 mg/L.